The experiences of selected professional women rugby and soccer players, and sport administrators during COVID-19 - Singh, K.; Singh, R. J. (From High-risk Sports to Sports as High Risk: Crisis, Captulation and Creativity during COVID-19, 2020)
Professional rugby and soccer for women in South Africa is still in the early stages of development. Therefore, these codes of sport for women are vulnerable to external influences such as the COVID-19 pandemic. This study focuses on the experiences that the COVID-19 pandemic has had on selected professional women`s rugby and soccer players and sport administrators. The theoretical approach that is adopted by this study is change theory whose central tenets are based on the work of Kurt Lewin (1947), considered the founding father of change management, and primarily focuses on approaching change management through the concepts of unfreeze, change, refreeze. The chapter also uses the work of Batras, Duff and Smith (2014) who offer a complementary theoretical perspective to Lewin and Rogers` (2003) concept of organisational change. Data for the study was collected from players and administrators. The sample consisted of female players (n=6)1 and two administrators (n=2) one for each sporting code. The total sample consisted of eight respondents. The data collection tools used were open-ended questionnaires (due to social distancing measures) which were separately designed for each category of respondents and a Twitter poll on whether COVID-19 had a negative impact on women`s sport. The Twitter poll was quantitatively analysed. The data from the open-ended questionnaires was qualitatively analysed using thematic analysis and linked to change theory in terms of the experiences of the participants in the face of a pandemic which has changed their normal way of playing and administering the different codes of sport. The findings of the study illuminate the financial impact on players who have contracts; the multiple psychological effect on players and the unpreparedness of administrators of women`s rugby and soccer to handle the uncertainties related to a pandemic of this nature. The study recommends the need for change and innovation for professional players and administrators in their approaches to these two codes of sports during the COVID-19 pandemic as well as the need for contingency planning measures drawing from the theoretical strands of change theory thinking: unfreeze, change, refreeze.